Lenalidomide treatment in relapsed/refractory B-cell lymphomas: A single center real-life experience - Merter, Mustafa; Uysal, Ayse (My University, 2022)
As an immunomodulatory drug, lenalidomide has been shown to have anti-lymphoma activity and is used in combination with several agents in the treatment of patients\rwith relapsed/refractory disease. In this study, we aimed to evaluate the efficiency of lenalidomide in the treatment of B-cell NHL. This retrospective study included patients with relapsed/refractory B-cell NHL who received lenalidomide treatment between March 2018 and January 2021. Patients’ demographic data, dose, and duration\rof the lenalidomide treatment, combined agents, response rates, side effects, and survival rates were evaluated. Twelve patients who diagnosed with relapsed/refractory\rNHL were included in the study. Lenalidomide treatment was initiated in combination with rituximab for nine of these patients and with temozolomide for the remaining\rthree of them. At the initiation of the lenalidomide treatment, patients’ median age was 72.5 (24-83) years. Number of females/males was 9/3. Nine of the patients were\rdiagnosed with diffuse large b-cell lymphoma (DLBCL), 3 of whom had isolated central nervous system lymphoma (CNS) and 1 had Richter transformation of chronic\rlymphocytic leukemia. Two patients were diagnosed with mantle cell lymphoma (MCL) and 1 patient was diagnosed with marginal zone lymphoma. The median treatment duration was 4 (1-20) months. In the response assessment, 4 patients had complete response while progressed disease was observed in 5 patients. Three patients\rdied before response assessment. In the median 33-month follow-up, progression-free survival and total survival were found as 4 (1-20) and 7 (1-22) months respectively.\rDue to its low toxicity profile and activity, lenalidomide could be a good option especially for elderly and fragile B-cell lymphoma patients. It is an agent to be considered\rparticularly in lymphomas with CNS involvement with its good CNS penetration. Its synergistic effect may give better results when used in combination with several\ranti-lymphoma drugs.
Keywords: Genel ve Dahili Tıp; Onkoloji; İmmünoloji